CULTURE, MEDIA AND POWER: UNDERSTANDING COMMUNITY SERVICE THROUGH MEDIA REPRESENTATION - Irish D Bautista (The Indonesian Journal of Communication Studies, 2015)
The study aims to examine the culture and ideological underpinnings espoused by Newsette, the official publication of De La Salle University-Dasmariñas (DLSU-D), through examination of headlines of articles pertaining to the promotion of culture of community extension service of DLSU-D. Specifically, it aims to: (1) define the ideology espoused on community service; (2) determine the linguistic concepts; (3) and examine the manipulation techniques used by the publication to its readers. Data were obtained through discourse analysis of the publication’s headlines. Analysis of this study allows an understanding of the standpoint of Newsette on community development endeavors of the University. It identifies salient points in illuminating messages which are revealing of the social and cultural representations on community services in the University. More importantly, the results provide building material for opinion and explanation of the impression, acceptance and participation of Lasallians towards community extension services.